A Comprehensive Review on Barium Titanate Nanoparticles as a Persuasive Piezoelectric Material for Biomedical Applications: Prospects and Challenges. Issue 12 (30th December 2022) - Sood, Ankur; Desseigne, Margaux; Dev, Atul; Maurizi, Lionel; Kumar, Anuj; Millot, Nadine; Han, Sung Soo
Abstract: Stimulation of cells with electrical cues is an imperative approach to interact with biological systems and has been exploited in clinical practices over a wide range of pathological ailments. This bioelectric interface has been extensively explored with the help of piezoelectric materials, leading to remarkable advancement in the past two decades. Among other members of this fraternity, colloidal perovskite barium titanate (BaTiO3 ) has gained substantial interest due to its noteworthy properties which includes high dielectric constant and excellent ferroelectric properties along with acceptable biocompatibility. Significant progression is witnessed for BaTiO3 nanoparticles (BaTiO3 NPs) as potent candidates for biomedical applications and in wearable bioelectronics, making them a promising personal healthcare platform. The current review highlights the nanostructured piezoelectric bio interface of BaTiO3 NPs in applications comprising drug delivery, tissue engineering, bioimaging, bioelectronics, and wearable devices. Particular attention has been dedicated toward the fabrication routes of BaTiO3 NPs along with different approaches for its surface modifications. This review offers a comprehensive discussion on the utility of BaTiO3 NPs as active devices rather than passive structural unit behaving as carriers for biomolecules. The employment of BaTiO3 NPs presents new scenarios and opportunity in the vast field of nanomedicines for biomedical applications. Abstract : A comprehensive review highlighting the nanostructured piezoelectric biointerface of barium titanate nanoparticles (BaTiO3 NPs) in applications comprising drug delivery, tissue engineering, bioimaging, bioelectronics, and wearable devices. The article presents different fabrication routes of BaTiO3 NPs along with diverse approaches for its surface modifications. Further, the toxicity assessment, dosage requirements, and bottlenecks in the clinical translation BaTiO3 NPs are meticulously discussed.